G123(P) Improving standards of care in early onset neonatal sepsis. (7th April 2014) - Verow, R; Woodgate, L; Nicholl, R
Abstract : Aim: Guidance on preventing and managing early-onset neonatal sepsis was outdated and confusing, leading to: variation in practice, inappropriate antibiotic use, prolonged inpatient stay, and suboptimal management of suspected sepsis. Method: Management of early-onset neonatal sepsis practice was audited against published NICE guidance in September 2012 for all preterm and term neonates on the postnatal ward. The primary standard was indication for commencing antibiotics as per criteria set out by NICE, with secondary standards of initial and 36hr C-reactive protein (CRP), blood culture (BC) and lumbar puncture (LP) results, antibiotic duration, whether daily paediatric review occurred, documented advice to parents at discharge and whether GP discharge summary was written. Results were reviewed alongside NICE guidance and neonatologists, obstetricians and microbiologists were consulted before formulating new guidance. Following analysis and implementation of changes, practice was re-audited in May 2013. Results: 46 neonates were commenced on antibiotics pre-guideline introduction, 2 were then excluded as notes were not available. 28 neonates were commenced on antibiotics post-guideline, 3 were then excluded due to unavailable notes. The number of births in each month were comparable. The proportion meeting the criteria for commencing antibiotics was significantly improved post-guideline introduction (100% vs 61%, p < 0.01). Secondary standards showed a trend of improvement post-guideline introduction with documented advice to parents significantly improving (32% vs 6.8%, p = 0.01). Conclusions: Unified guidelines promote confidence in managing early-onset sepsis, improving patient safety and engaging adherence to guidelines to facilitate change. Workload for neonatal nursing staff is reduced and guidance allows easier decision-making for junior medical staff. Overall, reviewing the need for antibiotics in the management of suspected and confirmed neonatal sepsis decreases inappropriate antibiotic usage. To maintain and improve standards, a septic care-bundle is being introduced to link in with the new transitional care unit.